2018
DOI: 10.1073/pnas.1803152115
|View full text |Cite
|
Sign up to set email alerts
|

Altered conformational landscape and dimerization dependency underpins the activation of EGFR by α C– β 4 loop insertion mutations

Abstract: Mutational activation of epidermal growth factor receptor (EGFR) in human cancers involves both point mutations and complex mutations (insertions and deletions). In particular, short in-frame insertion mutations within a conserved αC-β4 loop in the EGFR kinase domain are frequently observed in tumor samples and patients harboring these mutations are insensitive to first-generation EGFR inhibitors. Despite the prevalence and clinical relevance of insertion mutations, the mechanisms by which these mutations regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 67 publications
4
63
0
Order By: Relevance
“…Interestingly, we also found that all amino acid changes in our study occurred in a region located after the C‐helix of the EGFR tyrosine kinase domain. Recent studies reported that EGFR exon 20 insertions in this region were constitutive activating mutations . Therefore, this suggested that EGFR exon 20 insertions in SIP may promote epithelial cell proliferation, differentiation, or even malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we also found that all amino acid changes in our study occurred in a region located after the C‐helix of the EGFR tyrosine kinase domain. Recent studies reported that EGFR exon 20 insertions in this region were constitutive activating mutations . Therefore, this suggested that EGFR exon 20 insertions in SIP may promote epithelial cell proliferation, differentiation, or even malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that EGFR exon 20 insertions in this region were constitutive activating mutations. 21,22 Therefore, this suggested that EGFR exon 20 insertions in SIP may promote epithelial cell proliferation, differentiation, or even malignant transformation. Future studies are required to evaluate the downstream effects of EGFR exon 20 insertions in SIP.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative sequence studies have hypothesized that the αC‐β4 loop is coupled with protein kinase activation by regulating inter‐lobe movement and αC dynamics . Supporting this notion, biophysical and biochemical studies suggest that the αC‐β4 loop maintains auto‐inhibitory interactions to prevent inadvertent kinase activation .…”
Section: Disease Variants In the αC‐β4 Loopmentioning
confidence: 99%
“…Extended αC‐β4 loops are most commonly found in the CK1 and CMGC groups (Figure a) usually in the form of a short helical insert (Figure b). In many cases, extended αC‐β4 loops seem to be linked to constitutive enzyme activity . Table shows a list of kinases containing an extended αC‐β4 loop.…”
Section: Conservation and Variation In The αC‐β4 Loop Of Protein Kinasesmentioning
confidence: 99%
“…Patients with other, less common-activating mutations such as exon 20 insertions show no benefit from EGFR TKIs (see e.g. mycancergenome.org) despite EGFR being effectively dephosphorylated [8-10]. Apart from this mutation-specificity, there also a drug-specificity of clinical responses: where several EGFR-TKIs (erlotinib, gefitinib, afatinib, dacomitinib and osimertinib) have provided clinical benefit to EGFR -mutated pulmonary adenocarcinoma patients, a phase II study on lapatinib did not show any sign of clinical activity [10-12].…”
Section: Introductionmentioning
confidence: 99%